Heat Stress in Legume Seed Setting: Effects, Causes, and Future Prospects - Liu, Yonghua; Li, Jiajia; Zhu, Yulei; Jones, Ashley; Rose, Ray J.; Song, Youhong (Frontiers in Plant Science, 2019)
Grain legumes provide a rich resource of plant nutrition to human diets, and are vital for food security and sustainable cropping. Heat stress during flowering has a detrimental effect on legume seed yield, mainly due to irreversible loss of seed number. To start with, we provide an overview of the developmental and physiological basis of controlling seed setting in response to heat stress. It is shown that every single process of seed setting including male and female gametophyte development, fertilization and early seed/ovary development is sensitive to heat stress, in particular male reproductive development in legume crops is especially susceptible. A series of physiochemical processes including heat shock proteins, antioxidants, metabolites and hormones centered with sugar starvation are proposed to play a key role in regulating legume seed setting in response to heat stress. The exploration of the molecular mechanisms underlying reproductive heat tolerance is in its infancy. Medicago truncatula, with a small genome and well-established transformation system, emerged as a valuable model in testing gene function. Thus the clarification of physiological mechanisms and Medicago transformation platform enable to advance the molecular understanding of legume reproductive heat tolerance.